COMPUTATIONAL AND EXPERIMENTAL EVALUATION OF TECHNICAL CHARACTERISTICS OF TRUCKS TIRES - Z. A. Godzhaev; S. V. Goncharenko; D. Kh. Valeev; V. S. Karabtsev (Сельскохозяйственные машины и технологии)
Now improvement of technological design specification of trucks tires develops very much. In modern mechanical engineering polyamide and kapron cords for tires of line-haul trucks and buses are replaced with all-metal ones (AMC) even more often. It was defined that at increase in AMC tires production their technical characteristics were investigated insufficiently. In this regard there were carried out bench tests to compare the main operational indicators of domestic (JSC Nizhnekamskshina production) and foreign tires with an all-metal cord: 315/60R22.5 the NF-201 model with 315/60r22.5 the XZA2 ENERGY Michelin model (steering); 315/60R22.5 the NR-201 model with 315/60R22.5 the XDA2+ ENERGY Michelin model (drive); 315/80R22.5 the NF-201 model with 315/80R22.5 the 3D Michelin XZE X MultiWay model (steering); 315/80R22.5 the NR-201 model with 315/80R22.5 the 3D XDE X MultiWay model (drive). The laboratory researches were carried out for the purpose of an assessment of the universal, load, damping (hysteresis) and other characteristics of tires with use of the universal functional SIB-1M test-bench. It was established that Michelin AMC tires of steering low-profile 315/60R22.5 XZA2 ENERGY models have the best indicators on power heterogeneity - 0.47-0.89 percent. The high-profile AMC tires of drive wheels 315/80R22.5 of the NR-201 model of JSC Nizhnekamskshina have the worst indicators. However, all the tested tires correspond to GOST 5513-97on this indicator. It was noted that Nizhnekamsk AMC tires of the size 315/60R22.5 are flush with AMC tires Michelin on set of operational indicators, except power heterogeneity, and last one of Michelin tires is lower than Nizhnekamsk ones by 2-3 times. It was suggested to conduct further researches on definition of optimum operational tires indicators because of an intensive use of KAMAZ trucks in agricultural production